Space assessment of the University of the Philippines College of Mass Communication Library - Marco, Dianne Mae A. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
Libraries today are being carefully designed to meet the needs of the clients and also be able to house the different kinds of materials and collections of the organization and/or institution to which it is connected. Libraries continue to respond to the needs of its users; from updating its collection and services to upgrading and redesigning furniture, equipment, and the overall space allocations. It is in this light that this study focused on the way library users of the University of the Philippines College of Mass Communication Library use the spaces and behave towards it. This study is a quantitative research which collected data through tallying the number of users in a space every fifteen minutes; it also assesses and analyzes the spaces of the UP Mass Communication Library. It uses an observational design to examine the behavior of the users in using the spaces inside the library. The library has an estimated 1,500 clients including the students of the college, non-students, members of the faculty, and researchers in the unit library. This study uses the floor plan of the library in mapping the zones in the library. The data gathered from the observation showed that Study and Laptop and Study Zones are the most preferred zones in the library. It revealed that the spaces available in first floor of the library are the most used ones by the library users. The data also revealed that some of the library users now go to the library not to borrow materials available there or to avail the services like the usage of computers because users already have their own laptop and they bring their own study materials.